OPTIMIZATION OF ZIS FUND COLLECTION AT LAZISMU GRESIK REGENCY, INDONESIA, TO IMPROVE THE NATIONAL ZAKAT INDEX - Walid In'am Ahmad; Sirajul Arifin; Mugiyati (Airlangga International Journal of Islamic Economics and Finance, 2026)
This study aims to analyze the optimization strategy of ZIS fund collection at LAZISMU in Gresik Regency and how it impacts the increase in the national zakat index. The research method uses a qualitative approach based on literature review studies. This study aims to understand individual and group behavior relate to ZIS fund collection within natural institutional setting through a literature review approach. The originality of this study lies in its specific focus on local zakat institutions, particularly LAZISMU Gresik, which has rarely been the subject of in-depth academic study in relation to its contribution to the National Zakat Index. The finding reveals that optimizing ZIS fund collection requires strategic planning, community-based innovation such as the KOMDIG LAZ model, and local engagement to significantly enhance zakat collection outcomes. However, the study is limited by its reliance on secondary data and literature review, which may not fully capture the dynamic practices and challenges in the field. Practically, the findings provide useful insights for zakat institutions, especially local LAZ, to develop effective and scalable fundraising strategies that can contribute more directly to national zakat development indicators.